The Good, the Bad, and the Pandemic: An Intra-Group Approach to Exploring Students’ Experiences with Collaborative Learning During COVID-19 - Anghel, Ella (Teaching and Learning Inquiry, 2023)
Collaborative learning is increasingly common in higher education, with several studies pointing to its effectiveness. However, it also poses some social and cognitive challenges for students, resulting in students’ mixed attitudes toward collaborative learning. COVID-19 has added to these challenges by, for example, introducing barriers to face-to-face communication. Existing studies exploring the impact of COVID-19 on students’ experiences with collaborative learning focus on individual students, missing potential intra-group trends that could be useful to instructors. Using both Likert-style and open-ended questions, this study explored 38 college students’ experiences engaging in collaborative learning during COVID-19 both individually and at the intra-group level. Overall, students’ experiences were positive both academically and socially, though some experienced challenges such as freeloading and online connection issues. For most groups, there were one or two students who had negative experiences, but these issues seemed to be individual and not indicative of a group-level problem. The study introduces an intra-group approach to collaborative learning research. Its findings suggest that instructors should apply collaborative learning pedagogies to enhance students’ learning and social connectedness. Instructors could further improve students’ experiences by identifying and solving common issues (e.g., freeloading, technical difficulties) by surveying students or encouraging them to share these difficulties with the instructor. Click here to read the corresponding ISSOTL blog post.